2018
DOI: 10.1111/flan.12326
|View full text |Cite
|
Sign up to set email alerts
|

Future directions in assessment: Influences of standards and implications for language learning

Abstract: As Foreign Language Annals concludes its 50th anniversary, it is fitting to review the past and peer into the future of standards‐based education and assessment. Standards are a common yardstick used by educators and researchers as a powerful framework for conceptualizing teaching and measuring learner success. The impact of standards on language assessment, teaching, curricula, course design, and educational policy is indisputable, but can they even be more impactful, more beneficial? In this article, we refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Since course grades invariably include scores from in‐house and/or commercial test developers, it will be important that instructors and administrators possess a deep understanding of current knowledge of best practices in educational assessment and that they are able to formulate and justify a rationale for their chosen approach to assessment with accompanying instruments (see discussion in Malone, ). Moreover, as Cox, Malone, and Winke () have pointed out in their recent review article, contemporary language instructors not only need to demonstrate general assessment literacy but also need to find ways to align their assessments with widely accepted standards in L2 and foreign language education.…”
Section: Discussionmentioning
confidence: 99%
“…Since course grades invariably include scores from in‐house and/or commercial test developers, it will be important that instructors and administrators possess a deep understanding of current knowledge of best practices in educational assessment and that they are able to formulate and justify a rationale for their chosen approach to assessment with accompanying instruments (see discussion in Malone, ). Moreover, as Cox, Malone, and Winke () have pointed out in their recent review article, contemporary language instructors not only need to demonstrate general assessment literacy but also need to find ways to align their assessments with widely accepted standards in L2 and foreign language education.…”
Section: Discussionmentioning
confidence: 99%
“…More than a decade later, the findings by Kissau () support this claim: Several instructor candidates in his study complained that while they found the advanced language course required in their instructor preparation program to be interesting, few opportunities to actually use the language were provided and thus these courses did little to enhance their proficiency. Multiple reports have suggested that this mismatch between instructor candidates’ needs and commonly used pedagogies in departments of languages and literature contributes to the underperformance of aspiring world language instructors on the OPI (Cox, Malone, & Winke, ; Glisan et al, ; Huhn, ; Kissau, McCullough, Salas, & Pyke, ). Others (García, Hernández, & Davis‐Wiley, ) have argued that best practices associated with oral proficiency development, including the integration of the world language standards (The National Standards Collaborative Board, ), ACTFL proficiency levels (ACTFL, , ), and performance assessments with regular feedback must be infused into advanced content courses and not simply discussed and practiced in methodology courses for aspiring instructors.…”
Section: Review Of Literaturementioning
confidence: 99%
“…As “input is the sine qua non of acquisition” (Gass & Mackey, , p. 181), it is of utmost importance to focus on providing input in various modalities in order to encourage development, making sure to include a wide variety of activities within the modalities, even if the current tests assess a restricted range of the skills. The outcomes here and from the other research (see Cox, Malone, & Winke, ) may point to the need of richer, video‐based listening tests and tests of speaking and writing that integrate video‐based listening as part of the assessment construct.…”
Section: Discussionmentioning
confidence: 76%
“…The Language Proficiency Flagship Initiative provided a new, current, and broader perspective on student proficiency, taking into account how teaching methodologies and student bodies have changed since Carroll's study in the 1960s. Publications that have resulted from this initiative range from a monograph (Winke & Gass, in press) and publications that focused solely on world language proficiency in higher education (Hacking & Tschirner, ; Isbell, Winke, & Gass, in press; Tschirner, , ; Winke, Gass, & Heidrich, in press) to articles that highlight the implications of large‐scale testing and assessment (e.g., Cox, Malone, & Winke, ; Hacking & Rubio, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation